COMPARISON OF DIFFERENT ACCOUNTING SYSTEMS: LAUR AND FADN - Duygu AKTÜRK; Ferhan SAVRAN; Elif YÖRÜSÜN; Elif DURAK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The present study was conducted to compare two different accounting systems (Laur Accounting System and Farm Accountancy Data Network (FADN) used to put forth activity outcomes of agricultural enterprises. These two systems were used to classify cost and income items of agricultural enterprises and calculation methods were compared. The survey data gathered through questionnaires made with selected enterprises constituted the material of the present study. Current findings revealed that different accounting system used to put forth annual activity outcomes of agricultural enterprises classified enterprise income and cost items in different fashions. In Laur Accounting System, enterprise costs are classified as fixed and variable costs. On the other hand in FADN system, costs are classified as intermediate consumption, amortizations and external costs. In Laur acciounting system, enterprise success criteria are considered as gross profit, net product and agricultural income. On the other hand in FADN system, gross enterprise profit, enterprise net value-added and enterprise family income are considered as the success criteria.